Enzymatic electrode-electrolyte interface study during electrochemical sensing of biomolecules - Kumar A.; Singh P.; Prakash R. (My University, 2025)
Enzyme-based electrochemical analysis involves electron transfer between enzymes and bioanalytes, whereby redox-active sites of enzyme catalyze the exchange process during reaction with biomolecules present at the interface of an electrode and a supporting electrolyte. To fulfill this purpose, we incorporated various experimental studies for glucose oxidation in the presence of glucose oxidase enzyme over a conducting materials-electrode interface using an electrochemical technique. It includes conducting polymers, nanometals, transition metal oxides, carbon-based layered materials, and transition metal oxide dichalcogenides like MoSe2 or its composites modified over Au, Pt, and glassy carbon electrodes. In this chapter, we incorporate the concepts of sensing application mainly using cyclic voltammetry and electrochemical impedance spectroscopic methods. Apart from these, plausible mechanisms of enzymatic reactions over modified electrodes during the oxidation of biomolecules (glucose) are also incorporated. Prior to these essential supporting structures, we also explain the basics of electrochemistry, various factors that affect the electrochemical phenomena, electrode fabrication processes, and issues and future prospects related to enzymatic reactions. This chapter deals with the essential knowledge of charge transfer and electrochemical phenomena at the enzymatic electrode-electrolyte interface. © 2020 John Wiley & Sons, Inc.